New targets of AMP-activated protein kinase. (1st February 2003) - Hue, L.; Beauloye, C.; Bertrand, L.; Horman, S.; Krause, U.; Marsin, A.-S.; Meisse, D.; Vertommen, D.; Rider, M.H.
Abstract : The discovery of the AMP-activated protein kinase (AMPK) more than a decade ago has shed much light on the cellular response to stresses characterized by a fall in the concentration of ATP and an increase in the AMP/ATP ratio. All conditions known to increase this ratio activate AMPK, whose major role is to act as an emergency signal to conserve ATP. It does so by inhibiting anabolic processes and by activating pathways producing ATP. In recent years, our laboratory has discovered new targets of AMPK. The purpose of this short review is to summarize our contribution to this field.